Escola experimental de tempo integral e gestão democrática : um estudo do cotidiano escolar - Vieira, Leandro Costa (2015)
The research presented here depicts everyday aspects of a school community in the Municipality of Corumbá, Mato Grosso do Sul. With the main objective to identify the strategies and joints related to democratic administration made up of the relationships between school and community, present in the construction and development of educational activities in the Special Program of Integral Education Corumbá. It was considered relevant in conducting the research, the study of the School Daily life as a relevant methodology for the interpretations regarding the occupation of space by the subjects of the school community. With the epistemological theoretical basis of research which authors such: Certeau (2014); Azevedo (2002-2003); Alves and Oliveira (2001, 2002) among other authors who work in these works, referring to the study of everyday school life. For the theoretical foundation in democratic management and Integral Education sought to references in Moll (2000, 2012); Freire (1996, 2011, 2012, 2014); Arroyo (2011, 2012); Silva; Silva (2012) and others related to the topic. The empirical research was made from observations, notes in a field diary, conversations and interviews with the subjects of the school and the neighborhood community, linking theory and practice as a basic construct in the process of research, showing how has given the democratic process school evidenced from three categories: Democracy; Power and Participation. The data collected, categorized and analyzed are the results shown from interpretations of how the school community realizes the democratic process in its broadest context. Prioritized a closer look to the actions relating to training in a liberating perspective, able to promote the autonomy of the subjects involved in the educational process, and also the full and integrated training of students for life. What can be considered is that there is a discourse of democracy which is not effective in practice. The community does not participate democratically the most important decisions of management, it was found that there is a movement of management and organization of vertical school work, although there are some strategies of participation that reveal much more a game of power and handling